Early detection of prion protein aggregation with a fluorescent pentameric oligothiophene probe using spectral confocal microscopy. Issue 6 (17th September 2020) - Stepanchuk, Anastasiia; Tahir, Waqas; Nilsson, K. Peter R.; Schatzl, Hermann M.; Stys, Peter K.
Abstract: Misfolding of the prion protein (PrP) and templating of its pathological conformation onto cognate proteins causes a number of lethal disorders of central nervous system in humans and animals, such as Creutzfeldt–Jacob disease, chronic wasting disease and bovine spongiform encephalopathy. Structural rearrangement of PrP C into PrP Sc promotes aggregation of misfolded proteins into β‐sheet‐rich fibrils, which can be visualized by conformationally sensitive fluorescent probes. Early detection of prion misfolding and deposition might provide useful insights into its pathophysiology. Pentameric formyl thiophene acetic acid (pFTAA) is a novel amyloid probe that was shown to sensitively detect various misfolded proteins, including PrP. Here, we compared sensitivity of pFTAA staining and spectral microscopy with conventional methods of prion detection in mouse brains infected with mouse‐adapted 22L prions. pFTAA bound to prion deposits in mouse brain sections exhibited a red‐shifted fluorescence emission spectrum, which quantitatively increased with disease progression. Small prion deposits were detected as early as 50 days post‐inoculation, well before appearance of clinical signs. Moreover, we detected significant spectral shifts in the greater brain parenchyma as early as 25 days post‐inoculation, rivaling the most sensitive conventional method (real‐time quaking‐induced conversion). These results showcase the potential of pFTAA staining combined with spectral imaging for screening of prion‐infected tissue. Not only does this method have comparable sensitivity to established techniques, it is faster and technically simpler. Finally, this readout provides valuable information about the spatial distribution of prion aggregates across tissue in the earliest stages of infection, potentially providing valuable pathophysiological insight into prion transmission. Abstract : Early detection of misfolded and aggregated prion protein might provide useful insights into pathophysiology of prion diseases. Here, we compared sensitivity of pentameric formyl thiophene acetic acid (pFTAA) combined with spectral imaging and analyses with conventional prion detection methods. We found that pFTAA fluorescence spectroscopy detected pathological changes as early as 25 days post‐inoculation, comparable to the most sensitive in vitro prion detection techniques. Our results show the capability of this method for simultaneous early detection of prion misfolding and spatiotemporal distribution of prion aggregates throughout the brain, in a relatively fast and simple manner.